A elaboração de estratégias de ensino a partir das zonas do perfil conceitual de vida - Rezende, Raphael Divino Ferreira de (2019)
The conceptual profile is a way of modeling the heterogeneity of thoughts or meanings attributed to a given concept. In doing so, the present work had as main objective to analyze the relationship between the zones of the conceptual profile of Life and the teaching strategies used in the learning process. The theory of the conceptual profile proposed by Mortimer (1994, 1995 and 2000) and the conceptual profile of Life elaborated by Coutinho (2005) constituted the theoretical and methodological framework of the research. The research method of this work was the case study, and for data collection two instruments were used: an open questionnaire and video recording of the classes taught during the research. The sample universe for the questionnaire was 33 students from the 1st grade of High School. The data collected in the questionnaire allowed the mapping of the zones of the conceptual profile of Life (external zone, internal zone and relational zone) of the students. From these three zones of the conceptual profile of Life were structured activities that composed the teaching strategies. The analysis of the answers to the questionnaires showed the predominance of the external zone in the students' ways of thinking. From the transcription of the classes, it was noticed that there was a improvement of knowledge of the students for the other zones of the profile, due to the wide discussion and debate about the concept during the activities. The results showed that the planning of the activities from the conceptions of the students within each zone of the conceptual profile allows a series of problems related to the learning process are foreseen, allowing the teacher a better use of the discussions in the classroom.